2023
DOI: 10.1111/gcb.16760
|View full text |Cite
|
Sign up to set email alerts
|

Climatic seasonality challenges the stability of microbial‐driven deep soil carbon accumulation across China

Abstract: Microbial residues contribute to the long‐term stabilization of carbon in the entire soil profile, helping to regulate the climate of the planet; however, how sensitive these residues are to climatic seasonality remains virtually unknown, especially for deep soils across environmental gradients. Here, we investigated the changes of microbial residues along soil profiles (0–100 cm) from 44 typical ecosystems with a wide range of climates (~3100 km transects across China). Our results showed that microbial resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 82 publications
(94 reference statements)
0
11
0
Order By: Relevance
“…Soil C (particularly SOC) is typically a critical factor that influences the soil TNC content. The key role of TN in influencing TNC was also confirmed by the results of the meta‐analysis (Cao et al., 2023; Wen et al., 2023). It was observed that the supply and restriction of substrates (TC and TN) were the main drivers for the microbial necromass C pool (Shao et al., 2021).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Soil C (particularly SOC) is typically a critical factor that influences the soil TNC content. The key role of TN in influencing TNC was also confirmed by the results of the meta‐analysis (Cao et al., 2023; Wen et al., 2023). It was observed that the supply and restriction of substrates (TC and TN) were the main drivers for the microbial necromass C pool (Shao et al., 2021).…”
Section: Discussionmentioning
confidence: 62%
“…Soil C (particularly SOC) is typically a critical factor that influences the soil TNC content. The key role of TN in influencing TNC was also confirmed by the results of the meta-analysis (Cao et al, 2023;Wen et al, 2023).…”
Section: Responses Of Total Microbial Necromass C To Droughtmentioning
confidence: 59%
See 3 more Smart Citations